2007
DOI: 10.1186/cc5437
|View full text |Cite
|
Sign up to set email alerts
|

Central venous pressure in a femoral access: a true evaluation?

Abstract: Hydrogen sulfide is produced endogenously by a variety of enzymes involved in cysteine metabolism. Clinical data indicate that endogenous levels of hydrogen sulfide are diminished in various forms of cardiovascular diseases. The aim of the current study was to investigate the effects of hydrogen sulfide supplementation on cardiac function during reperfusion in a clinically relevant experimental model of cardiopulmonary bypass. Twelve anesthetized dogs underwent hypothermic cardiopulmonary bypass. After 60 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…As the patient's coagulation parameters were abnormal, a subclavian approach was avoided because the subclavian veins are not amenable to external pressure when they bleed, unlike IJVs [ 1 ]. Although both femoral sites were available, the reliability of femoral vein CVP readings as a surrogate is controversial, except when the intra-abdominal pressure is < 15 mmHg [ 2 ]. Pacheco et al [ 3 ] found a linear relationship between the superior vena cava and femoral vein readings when the head is positioned at zero degrees immediately after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As the patient's coagulation parameters were abnormal, a subclavian approach was avoided because the subclavian veins are not amenable to external pressure when they bleed, unlike IJVs [ 1 ]. Although both femoral sites were available, the reliability of femoral vein CVP readings as a surrogate is controversial, except when the intra-abdominal pressure is < 15 mmHg [ 2 ]. Pacheco et al [ 3 ] found a linear relationship between the superior vena cava and femoral vein readings when the head is positioned at zero degrees immediately after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%